Pharmacokinetics of ketamine and norketamine enantiomers after racemic or S-ketamine IV bolus administration in dogs during sevoflurane anaesthesia. (June 2017) - Romagnoli, Noemi; Bektas, Rima N.; Kutter, Annette P.; Barbarossa, Andrea; Roncada, Paola; Hartnack, Sonja; Bettschart-Wolfensberger, Regula
Abstract: The aims of this study were to measure plasma levels of R- and S-ketamine and their major metabolites R- and S-norketamine following single intravenous bolus administration of racemic or S-ketamine in sevoflurane anaesthetised dogs and to calculate the relevant pharmacokinetic profiles. Six adult healthy beagle dogs were used in the study. An intravenous bolus of 4 mg/kg racemic ketamine (RS-KET) or 2 mg/kg S-ketamine (S-KET) was administered, with a three-weeks washout period between treatments. Venous blood samples were collected at fixed times until 900 min and R- and S-ketamine as well as R- and S-norketamine plasma levels determined by liquid chromatography coupled with tandem mass spectrometry. Cardiovascular parameters were recorded during the anaesthesia until 240 min. All dogs recovered well from anaesthesia. No statistical differences between groups were detected in any cardiovascular parameter. The pharmacokinetics of S-ketamine did not differ when injected intravenously alone or as part of the racemic mixture in dogs anaesthetised with sevoflurane. Following racemic ketamine, the area under the curve of R-norketamine was statistically higher than the one of S-norketamine. Highlights: In human and horses the pharmacokinetic profiles of racemic and S-ketamine are different PK data show no difference between racemic and S-ketamine in dog Cardiopulmonary parameters are identical in dog after S-ketamine at 50% dose or racemate